2015
DOI: 10.9775/kvfd.2014.12662
|View full text |Cite
|
Sign up to set email alerts
|

Erkek Ratlarda Maclura pomifera Ekstraktının Sisplatin ile Oluşturulmuş Üreme Sistemi Hasarı Üzerine Etkisi

Abstract: In this study, we aimed to investigate the effect of maclura pomifera (MP) (known as cytotoxic, anti-tumoural, anti-inflammatoric, antinociceptive, and anti-oxidative) extract upon the spermatological parameters in Cisplatin (anti-tumoural chemotherapeutic with Reactive Oxygen Species (ROS)-generating side-effects)-treated rats. A total of seventeen male Sprague Dawley rats, aged eight weeks and weighing 250-300 g, were used. Three experimental groups were assigned, as follows; Group 1 (n=5) as control (C): th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…This situation can be explained by that MTX damages cell membrane integrity by disturbing lipids and proteins within the sperm membrane. It was determined in previous studies that like MTX, Cisplatin causes a marked decrease in sperm density and motility [32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…This situation can be explained by that MTX damages cell membrane integrity by disturbing lipids and proteins within the sperm membrane. It was determined in previous studies that like MTX, Cisplatin causes a marked decrease in sperm density and motility [32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…Semen density was determined following the method described in our previous study . Briefly, 10‐µL of a semen sample was dropped in 990 µL PS and thus diluted to 1 of 100 in a centrifuge tube.…”
Section: Methodsmentioning
confidence: 99%
“…It is suggested that DOX treatment increases the production of quinone, a free radical that causes cytotoxicity . Reactive oxygen species (ROS) are required for some kind of physiological events such as sperm maturation, capacitation of sperm cells, and sperm‐oocyte interactions in physiological limits . Increased levels of ROS have negative effects on sperm cells.…”
Section: Introductionmentioning
confidence: 99%